2013
DOI: 10.1021/nl304495v
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Single Fe Atoms in Graphene Vacancies

Abstract: Focused electron beam irradiation has been used to create mono and divacancies in graphene within a defined area, which then act as trap sites for mobile Fe atoms initially resident on the graphene surface. Aberration-corrected transmission electron microscopy at 80 kV has been used to study the real time dynamics of Fe atoms filling the vacancy sites in graphene with atomic resolution. We find that the incorporation of a dopant atom results in pronounced displacements of the surrounding carbon atoms of up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
202
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(211 citation statements)
references
References 44 publications
(64 reference statements)
9
202
0
Order By: Relevance
“…The insertion of carbon atoms at the graphene edge through Fe highlights the catalytic properties of Fe at an atomic level. In this process, free carbon atoms in the vicinity diffuse through the assistance of the electron beam (7,31). Electrons accelerated through 80 kV can transfer up to 16 eV to a carbon atom and 3 eV to a single Fe atom (32).…”
Section: Resultsmentioning
confidence: 99%
“…The insertion of carbon atoms at the graphene edge through Fe highlights the catalytic properties of Fe at an atomic level. In this process, free carbon atoms in the vicinity diffuse through the assistance of the electron beam (7,31). Electrons accelerated through 80 kV can transfer up to 16 eV to a carbon atom and 3 eV to a single Fe atom (32).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the major source of the magnetism in two systems is quite different. These fascinating phenomenon, in combination with the fact that the substitutional 2D materials has been artificially synthesis by many groups [47][48][49][50][51][52][53], can paves a new route at nanoscale for novel functionalities of optical and spintronics devices.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, theoretical calculations have shown that it is a very interesting 2D material [7,8,25,26]. Moving down in the periodic table, Se [27,28], Ni [29,30], Mn [30], Fe [31], Co [30], were embedded in the graphene plane. Interestingly, even heavy elements like U and Th [32] were employed to dope graphene.…”
Section: Introductionmentioning
confidence: 99%